Interdisciplinarity in Environmental Psychology in human nature interrelation (Research, Society and Development, 2020)
Over the years, the relationship between man and the environment as his habitat has changed. In the face of globalization and technological advances, it is possible to perceive man's distance from nature. This work sought to understand the relations of man and the environment, in this case, the natural and projected environment, through a review of the theoretical concepts that originated from Environmental Psychology and that developed from it, with the objective of capturing the power that the environment it operates on man, the connection established with him, and the different ways of the subjects to act and react according to the environment in which they live. In methodological terms, the research was qualitative, basic, exploratory and bibliographic, and took place from May to July 2020. The results indicated that the analysis of human-environment relations, no matter how much they reveal their behaviors and morals, does not it is enough to understand how they mix with the world, how they experience phenomena. This understanding requires the search for interdisciplinary studies and practices, preserving the idea that nature and man are deeply connected and, therefore, keep a complementary relationship, and spaces must allow interaction, respect and awareness of care and ecological practices.